1997
DOI: 10.1002/(sici)1097-4636(19970915)36:4<454::aid-jbm3>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and morphologic investigation of the tensile strength of a bone-hydroxyapatite interface

Abstract: For load-bearing calcium-phosphate biomaterials, it is important to understand the relative contributions of direct physical-chemical bonding vs. mechanical interlocking to interfacial strength. In the limit of a perfectly smooth hydroxyapatite (HA) surface, a tensile test of the bone-HA interface affords an opportunity to isolate the bonding contribution related to HA surface chemistry alone. This study measured the bone-HA interfacial tensile strength for highly polished (approximately 0.05 micron alumina) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…Several studies have demonstrated that BCP is biocompatible with hard tissues and exhibits osteo-conductive properties. [1][2][3][4][5] BCP has been shown to form a direct bond with surrounding tissue after bone implantation. However, it has very poor mechanical properties, which severely limits its use in load-bearing implant applications.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that BCP is biocompatible with hard tissues and exhibits osteo-conductive properties. [1][2][3][4][5] BCP has been shown to form a direct bond with surrounding tissue after bone implantation. However, it has very poor mechanical properties, which severely limits its use in load-bearing implant applications.…”
Section: Introductionmentioning
confidence: 99%
“…titanium (Albrektsson et al 1981), titanium alloy (Takatsuka et al 1995), surface chemistrymodified c.p. titanium (Skripitz & Aspenberg 1998) and hydroxyapatite-coated implants (Edwards et al 1997). Our recent series of investigations on anionincorporated (sulphur or phosphorus) and cationincorporated (calcium or magnesium) titanium implants indirectly verified biochemical bonds in animal models (Sul 2003;Sul et al 2004Sul et al , 2005Sul et al , 2006Sul et al , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Bioceramics of naturally derived biological apatites are more economic. Extensive studies have indicated that HA is biocompatible with hard tissues of human beings and exhibits osteoconductive properties [4][5][6][7].…”
Section: Introductionmentioning
confidence: 96%